Integrated multi-omics analysis reveals insights into Chinese forest musk deer (Moschus berezovskii) genome evolution and musk synthesis - Feng, Hui; Feng, Tingyin; Mo, Yidi; Sun, Suli; Wang, Lu; Lu, Chunbin; Feng, Chengli; Xing, Ke; Su, Zhijian (Frontiers in Cell and Developmental Biology, 2023)
Among the artiodactyls, male animals belonging to the Family Moschidae have a unique tissue, the musk gland, with the capability of musk synthesis. However, the genetic basis of musk gland formation and musk production are still poorly understood. Here, musk gland tissues from two juvenile and three adult Chinese forest musk deer (Moschus berezovskii) were utilized to analyze genomic evolution events, evaluate mRNA profiles and investigate cell compositions. By performing genome reannotation and comparison with 11 ruminant genomes, three expanded gene families were identified in the Moschus berezovskii genome. Transcriptional analysis further indicated that the musk gland displayed a prostate-like mRNA expression pattern. Single-cell sequencing revealed that the musk gland is composed of seven distinguishable cell types. Among them, sebaceous gland cells and luminal epithelial cells play important roles in musk synthesis, while endothelial cells master the regulation of cell-to-cell communication. In conclusion, our study provides insights into musk gland formation and the musk-synthesizing process.